A praxeological analysis of linear equations in Indonesian mathematics textbooks: Focusing on systemic and epistemic aspect - Fardian, Dilham; Suryadi, Didi; Prabawanto, Sufyani (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2025)
Educational research has consistently highlighted that learning obstacles stem not only from the design of learning situations but also from curriculum structures and textbooks, which are pivotal learning resources. Despite the growing body of literature, limited studies focus on the specific challenges posed by the design of learning materials, particularly in early algebra within the Indonesian context. This study addresses the gap by analyzing the grade VII mathematics textbook in the Merdeka Curriculum, with a focus on linear equations with one variable, to uncover learning obstacles in early algebra. Utilizing Didactical Design Research (DDR), a qualitative approach, the research examines the praxeological components of the textbook—tasks (T), techniques (τ), technology (θ), and theory (Θ). The findings indicate three primary categories of learning obstacles: ontogenic, epistemological, and didactic. Notably, the analysis reveals that the design of linear equation content in the textbook is non-systemic and lacks epistemic coherence, posing significant challenges for learners. This study contributes to the understanding of curriculum design by identifying specific obstacles in the Merdeka Curriculum's grade VII mathematics textbook and underscores the need for more systemic and epistemically aligned textbook development. Future research should extend this analysis to other textbooks across various grade levels to determine if these findings are consistent within the broader curriculum framework.